Microwave assisted physico-chemical modification of Bentonite clay: characterization and photocatalytic activity. (2017) - Surendra, B.S.; Veerabhadraswamy, M.; Anil kumar, H.G.; Kendagannaswamy, B.K.; Nagaswarupa, H.P.; Prashanth, S.C.
Abstract: The Bentonite clay was modified with different concentrations of H2 SO4, forms acid activated Bentonite clay under microwave irradiation. These acid activation catalysts were characterized by PXRD, SEM, BET, FT-IR and UV Visible spectral analysis. The morphology of the catalysts was characterized by SEM analysis and was found to change particles significantly with microwave irradiation. PXRD studies revealed that the catalysts have dioctahedral phase and the average crystallite size is found to be in the range of 11-18 nm. The optical properties of the photocatalysts were investigated by UV–Vis; demonstrate the energy band gap of the catalyst. Microwave irradiation derived 2M H2 SO4 catalysts exhibited excellent UV induced photocatalytic performance for the degradation of Acid orange 8(AO 8). The catalytic activities were correlated with crystallite size, band gap, morphologies and oxygen vacancies of the catalyst. Modified clay photocatalysts with high activity for environmental clean-up and it can be re-used up to 3-4 times, further used in practical applications.